KARATERISTIK KERAPATAN DAN MORFOMETRIK Enhalus acoroides DI PERAIRAN TELUK BALIKPAPAN KALIMANTAN TIMUR - Rayhansyah, Muhammad Fauzan; Irawan, Aditya; Sari, Lily Inderia (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
This research was conducted in Oktober 2022 - January 2023 in the waters of Balikpapan Bay, East Kalimantan. The purpose of this study was to determine the density and morphometric characteristics of Enhalus acoroides in Balikpapan Bay waters. The results showed that the density of E. acoroides was 280 – 748 shoots/m2 which was included in the dense category. Determination of the research location was determined by purposive sampling method. Sampling of E. acoroides at each station was carried out at low tide by determining the transect line from the highest tide position to the lowest low tide. Determination of the density and morphometrics of E. acoroides at each sub-station using a 50 x 50 cm quadrant frame. The results of morphometric measurements of E. acoroides have leaf length characteristics ranging from 28.80 – 91.07 cm, leaf width ranging from 6.40 – 15.84 mm, stem length ranging from 16.76 – 81.84 mm, stem diameter ranging from 12, 21 – 19.73 mm, rhizome length ranges from 29.95 – 119.85 mm, rhizome diameter ranges from 7.52 mm – 13.74 mm, root length ranges from 48.32 – 105.73 mm, root diameter ranges from 1.50 – 3.19 mm, the number of roots ranges from 3 – 10 roots. The morphometrics of seagrass are influenced by the characteristics of the substrate and the availability of nutrients.